2019
DOI: 10.1016/j.amepre.2018.08.026
|View full text |Cite
|
Sign up to set email alerts
|

Implementing School-Based Policies to Prevent Obesity: Cluster Randomized Trial

Abstract: Introduction: Healthier school environments can benefit students, and school wellness policies may result in meaningful enhancements. Schools participating in federal child nutrition programs must implement wellness policies as mandated by law. The primary study objective is to assess effectiveness of implementing school-based nutrition and physical activity policies on student BMI trajectories. Study design: Cluster randomized trial using 2 × 2 factorial design. Setting/participants: Twelve randomly selected … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
50
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 48 publications
(55 citation statements)
references
References 34 publications
1
50
0
Order By: Relevance
“…Within schools, it is essential to implement policies that promote health through adopting healthy life style and disseminating health messages [18]. Culture was also found to have an effect in this study, two fathers expressed their levels of knowledge and involvement in their children's care differed.…”
Section: Discussionmentioning
confidence: 62%
“…Within schools, it is essential to implement policies that promote health through adopting healthy life style and disseminating health messages [18]. Culture was also found to have an effect in this study, two fathers expressed their levels of knowledge and involvement in their children's care differed.…”
Section: Discussionmentioning
confidence: 62%
“…Although every school in the country has a written policy but, several studies have found that strong written policies do not necessarily predict thorough implementation. So, University needs to collaborate with students to assist in the implementation and evaluation of school wellness policies after they have been written and approved [27].…”
Section: Interview Resultsmentioning
confidence: 99%
“…It required annual body mass index (BMI) screenings for all public school students, elimination of elementary school students’ access to vending machines, and creation of physical education and nutrition standards via district physical activity and nutrition committees along with input from a Child Health Advisory committee. 91 , 92 A study published in 2018 assessing the effectiveness of this policy concluded that it was very unlikely that the Arkansas Act was having an impact on preventing adolescent overweight and obesity. 93 …”
Section: School-based Interventionsmentioning
confidence: 99%